Impact Dynamics of Binary Off-Center Unequal-Sized Droplets Colliding on a Superhydrophobic Surface (Advances in Applied Mathematics and Mechanics, 2024)
We present a numerical study that investigates the collision between a fallingdroplet and a sessile droplet on a superhydrophobic surface with various impact velocities, size ratios, and eccentric angles. After impact, the two droplets may mergeinto a bigger droplet. We use the OpenFOAM volume of the fluid method to monitorthe droplet geometry, analyze the dynamic characteristics of the impact, determine thecontact time of the merged droplet on the surface, and locate the contact line of themerged droplet. When a large droplet impacts a small droplet, increasing the eccentric angle decreases both the maximum spreading distance and the contact time for allimpact velocities. Additionally, it reduces the number of broken small droplets thatsplash following fragmentation at high impact velocity. Droplets of equal size produce impacts that are nearly the same as those of a large droplet impacting a smalldroplet. The only difference occurs at the moment of droplet fragmentation. When asmall droplet impacts a large droplet, increasing the eccentric angle by less than $10^{°}$ shortens the maximum spreading distance while only slightly increasing the contacttime. In addition, droplet fragmentation is significantly reduced. The results provideinsight into potential applications of droplet-solid interactions, which are valuable forengineering applications such as anti-icing and self-cleaning.